Amplifying the Black Voice Through Design - Terresa Moses (Diseña, 2022)
Minneapolis experienced another devastating occurrence: the murder of an unarmed black man by the police in the midst of the national trial of Derek Chauvin. While the community continued to grieve the injustices against George Floyd, police officer Amy Potter shot and killed Daunte Wright on April 11th, 2021. To inspire unity amongst organizers and protestors, I created typography inspired by the Movement for Black Lives, and messages to unify what we all were, and still are, fighting for. My work is open-source and used on t-shirts, hoodies, posters, and pins, which I organized to be distributed for free within the community. Throughout this visual essay, I will discuss the importance of community protest as a tool for racial justice, and how design can provide an opportunity to support and uplift the voice of Black people.